PENGARUH KESIAPAN ORGANISASI, TEKANAN EKSTERNAL, DAN MANFAAT DIRASAKAN PADA ADOPSI E-COMMERCE UMKM TERHADAP PENDAPATAN OPERASIONAL - Noviyanti, Lidya; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2025)
Batam is one of the cities with a high economic growth rate in Indonesia. MSMEs in Batam City can be seen from various sector developments, both through economic, social, and government policies. Batam City is often known as a city of industry and international trade, because of its proximity to Singapore and Malaysia which makes Batam City a strategic economic center. This study aims to examine the influence of organizational readiness, external pressure, and perceived benefits on the adoption of MSME E-commerce on operating income. The sample in this study is MSME actors in Batam Kota District, Batam City. Hereby, the researcher uses quantitative research methods by collecting and disseminating data. The data in question is the filling out of a questionnaire, where in the study with 163 respondents. After the data is obtained, it will continue to be tested using SPSS version 25. The results of this study show that organizational readiness affects operational income, external pressure affects operational income, and benefits are felt in the adoption of E-commerce MSMEs. Simultaneously, the three variables can be known as the value of f-table is 3.05, the f-count is 1.414, and the significant value obtained is <0.001 where the value is less than 0.05. Therefore, it can be said that the variables of Organizational Readiness (X1), External Pressure (X2), and Perceived Benefits on MSME E-commerce Adoption (X3) simultaneously have a significant effect on Operating Income (Y). The conclusion based on the research states that H1 is Accepted, H2 is Accepted, H3 is Accepted, and H4 is Accepted.